Absence of Human Papillomavirus Infection and Activation of PI3K-AKT Pathway in Cervical Clear Cell Carcinoma. Issue 6 (1st July 2013) - Ueno, Sayaka; Sudo, Tamotsu; Oka, Noriko; Wakahashi, Senn; Yamaguchi, Satoshi; Fujiwara, Kiyoshi; Mikami, Yoshiki; Nishimura, Ryuichiro
Abstract : Objective: Cervical cancer is the second most common cancer in females worldwide, and the majority of squamous cell carcinomas and adenocarcinomas are associated with high-risk human papillomavirus (HPV) infection. However, the relationship between clear cell carcinoma of the cervix (CCCC) and HPV is unclear. In this study, we sought to determine if HPV infection is associated with CCCC and to elucidate the signaling pathways involved. Methods: We collected samples from 13 CCCC patients and collated the relevant clinicopathologic data. We then evaluated the presence of HPV types 16, 18, 31, 33, 35, 52, and 58 by broad-spectrum amplification by polymerase chain reaction and HPV types 39, 45, 51, 56, 59, and 68 by nested polymerase chain reaction assay that combines degenerate E6/E7 consensus primers and type-specific primers from extracted genomic DNA. Immunohistochemistry was used to analyze the expression of EGFR (epidermal growth factor receptor), HER2, PTEN (phosphatase and tensin homolog), phospho-AKT, phospho-mTOR (mammalian target of rapamycin), p16 INK4a, and p53. EGFR and HER2 gene amplification was determined by fluorescence in situ hybridization. Results: Patients with stage IB CCCC had a better 3-year overall survival rate compared with those with advanced-stage cancer (100% vs 44%; P = 0.014). High-risk HPVs were not detected in any of the cases examined. EGFR immunostaining was observed in 9 (75%) of 12 patients, HER2 in 3 (25%) of 12, PTEN in 6 (50%) of 12, and phospho-AKT in 7 (58%) of 12, and phospho-mTOR in 6 (50%) of 12. EGFR amplification could not be detected, but HER2 amplification was identified in 1 of (12.5%) 8 cases. Conclusions: Patients with stage I CCCC demonstrated good overall survival and rare recurrence. Clear cell carcinoma of the cervix is unrelated to high-risk HPV infection; hence, current vaccines will not prevent the incidence of CCCC. However, increased EGFR or HER2 expression or activation of AKT or mTOR was observed in all cases, indicating that inhibitors of tyrosine kinases or the AKT-mTOR pathway may be suitable treatment regimens for CCCC.